China’s energy cooperation within the 17+1 - Katarina Zakić; Nevena Šekarić Stojanović (Međunarodni Problemi, 2021)
The paper analyses Chinese energy cooperation within the 17+1 Cooperation Framework. In order to present the broader political context of this collaboration, special attention is given to Chinese energy interests and EU energy policy. Since the existing databases about Chinese energy projects in 17+1 were incomplete, the authors created a new dedicated database. The authors address key questions about the principal projects involved such as: what are the countries and energy subsectors in which China invests the most; what are the main obstacles in existing energy cooperation; does this kind of energy cooperation have a positive impact on the development of 17+1 members and is China successful in fulfilling its geo-economic strategy in 17+1 in regards to its overall energy policy. The authors find that China is primarily interested in building coalfired power plants, but results remain below expectations, with performance affected by a combination of EU opposition, project costs, and internal political issues in the 17+1 countries. The nuclear energy subsector is where Chinese enterprises have experienced some of their greatest failures, while the hydro energy subsector still has potential for future development. In addition, China is strongly investing in green energy and slowly but surely achieving its energy policy goals as part of its broader geo-economic strategy. The authors conclude that the overall effects of cooperation in the energy field are promising, but there is still space for further improvement.